An Evaluation of the Performance of Lateritic Soil Stabilized with Cement and Biochars to be Used in Road Bases of Low-Volume Sealed Roads - Otieno, Meshack; Gariy, Zachary; Kabubo, Charles (Engineering, Technology & Applied Science Research, 2023)
The study investigated the effects of adding Saw Dust Ash (SDA) and Sugar Cane Bagasse Ash (SCBA) on the strength of cement with stabilized lateritic soil. The experiments carried out in both the lateritic soil and stabilized lateritic soil considered Atterberg limits, sieve/hydrometer analysis, compaction, soaked California Bearing Ratio (CBR), and Unconfined Compressive Strength (UCS) at various curing periods. Ordinary Portland Cement (OPC) was introduced into the soil with varying content (0%, 3%, 5%, 7%, and 9%) by weight of the soil sample. The results showed that CBR and UCS increased to 175.7% and 1.999 MPa, respectively, as the OPC content increased to 7%. The optimal OPC content to meet the 1.5MPa UCS requirement for road bases on low-volume sealed roads in Kenya was 7%. The next treatment involved partially replacing the OPC content with SDA and SCBA in different doses (7-0-0%, 5-1-1%, 3-2-2%, 1-3-3%, and 0-3.5-3.5%, respectively) for various curing periods. The results showed that CBR and UCS decreased as the OPC content decreased and SCBA and SDA increased. At a content of 5% OPC, 1% SDA, and 1% SCBA, UCS and CBR were 1.877 MPa and 149%, respectively, suggesting that it was the optimal dosage to meet the 1.5MPa UCS requirement for road bases on low-volume sealed roads in Kenya. The durability test indicated that the specimens treated with 5% OPC, 1% SDA, and 1% SCBA met the 80% durability index mark, as recommended for cement-stabilized soils. Previous studies used SDA and SCBA separately with cement or lime to stabilize the subgrade or subbase of roads, but this study focused on using these materials together as a partial OPC replacement to stabilize lateritic road bases for use in low-volume sealed roads. The goal was to use local agricultural and industrial waste materials in road construction and improve the strength characteristics of road bases while preserving the environment through waste utilization.